Prospective Associations Between Dietary Antioxidant Intake and Frailty in Older Australian Men: The Concord Health and Ageing in Men Project. (6th April 2019) - Das, Arpita; Cumming, Robert G; Naganathan, Vasi; Blyth, Fiona; Ribeiro, Rosilene V; Le Couteur, David G; Handelsman, David J; Waite, Louise M; Simpson, Stephen J; Hirani, Vasant
Abstract: Background: The objective of the study is to evaluate the prospective associations between antioxidant intake and incident frailty among older Australian men aged ≥75 years. Methods: Seven hundred and ninety-four men participated in a detailed diet history interview at the Concord Health and Ageing in Men Project (CHAMP) study third wave (considered baseline nutrition here) and 781 men participated at the fourth wave (considered 3-year follow-up here). The main outcome measurement was incident frailty at 3-year follow-up, using the Cardiovascular Health Study definition. Dietary adequacy of antioxidant intake was assessed by comparing participants' median intakes of four dietary antioxidants (vitamin A, E, C, and zinc) to the nutrient reference values (NRVs). Attainment of the NRVs was incorporated into a dichotomized variable "poor" (meeting ≤2 antioxidants) or "good" (meeting ≥3 antioxidants) as the independent variable using the cut-point method. Also, intakes of each individual dietary antioxidant at baseline nutrition were categorized into quartiles. Analyses were performed using multinomial logistic regression. Results: Incidence of pre-frailty was 53.0% and frailty was 6.4% at 3-year follow-up. Poor dietary antioxidant intake (meeting ≤2) at baseline nutrition was associated with incident frailty at 3-year follow-up in unadjusted (OR: 2.59 [95% CI: 1.47, 4.59, p = .001]) and adjusted (OR: 2.46 [95% CI: 1.10, 5.51, p = .03]) analyses. The lowest quartile of vitamin E intake (<7.08 mg/d) was significantly associated with incident frailty (OR: 2.46 [95% CI: 1.01, 6.00, p = .05]). Conclusions: Poor antioxidant intake, particularly vitamin E, is a plausible factor associated with incident frailty among older men. This supports the need for clinical trials of diets rich in antioxidants or possibly low-dose antioxidant supplements, for prevention of frailty.